Physalin B Suppresses Inflammatory Response to Lipopolysaccharide in RAW264.7 Cells by Inhibiting NF-κB Signaling - Yanjun Yang; Lang Yi; Qing Wang; Bingbing Xie; Congwei Sha; Yan Dong (Journal of Chemistry)
Physalin B from Physalis angulata L. (Solanaceae) is a naturally occurring secosteroid with multiple biological activities. But its anti-inflammatory activity and mechanism remain unclear. Physalin B effects on RAW264.7 macrophages stimulated by lipopolysaccharide (LPS) were observed in this study. The expression and secretion of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) induced by LPS were significantly inhibited by physalin B. Meanwhile, the NF-κB nuclear translocation induced by LPS was inhibited by physalin B. The anti-inflammatory effects of physalin B could not be inhibited by mifepristone (RU486), the blocker of glucocorticoid receptor. In conclusion, physalin B can suppress inflammatory response to LPS in macrophages by inhibiting the production of inflammatory cytokines via NF-κB signaling.